Path analysis of the core competency of thai private hospitals in the ASEAN economic community - Ponanake, Pareeyawadee; Limnararat, Sunpasit; Pithuncharurnlap, Manat; Sangmanee, Woranat (My University, 2014)
The objectives of the research were to study path relations between a lean healthcare system, Six Sigma practice and internal quality management of core competency of Thai private hospitals to be an ASEAN Economic Community (AEC) medical care center. The population and sample group of the study were the Hospital Accreditation (HA) officers of Thai private hospitals between December 2012 and May 2013. The sample group totaled 312 persons. The study tool included questionnaires and a path analysis was employed to analyze the data. The findings of the study determined that (1) The lean healthcare system indirectly influences, through internal quality management, a hospital's core competency to be an AEC medical care center, (2) Six Sigma practices directly influence a hospital's core competency to be an AEC medical care center, (3) Six Sigma practices indirectly influence, through internal quality management, a hospital's core competency to be an AEC medical care center, (4) Internal quality management directly influences a hospital's core competency to be an AEC medical care center.
Keywords: AEC; Core competency; Internal quality management; Lean healthcare; Medical care center